2004
DOI: 10.1081/dct-120030725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organophosphorus and Organochlorine Pesticides (Monochrotophos, Chlorpyriphos, Dimethoate, and Endosulfan) on Human Lymphocytes In‐Vitro

Abstract: The toxicological profile of the four pesticides described herein characterizes its effects on lymphocytes from peripheral blood from healthy donors. The exposure to all pesticides was by direct interaction/incubation with varying concentrations of the pesticide with blood sample in-vitro. The dose response relationship in each case was calculated by applying log tables as LC50 values. Cytotoxicity of these pesticides on lymphocytes was measured using the trypan blue dye exclusion technique. Based on LC50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 15 publications
2
51
1
Order By: Relevance
“…Previous studies have affi rmed the genotoxic and/or cytotoxic effects of Type II pyrethroids such as cyfl uthrin, cypermethrin etc. (4)(5)(6)(7)(8)(9). The carcinogenic potential of pyrethroids was also reported on the murine model (9).…”
mentioning
confidence: 97%
“…Previous studies have affi rmed the genotoxic and/or cytotoxic effects of Type II pyrethroids such as cyfl uthrin, cypermethrin etc. (4)(5)(6)(7)(8)(9). The carcinogenic potential of pyrethroids was also reported on the murine model (9).…”
mentioning
confidence: 97%
“…The comet assay is increasingly used in industrial genotoxicity in vitro. In vitro technologies have been used for determining various end points like DNA damage, cytotoxicity and chromosomal aberration frequencies (Jamil et al, 2004).…”
Section: Single Cell Gel Electrophoresis (Scge) or Comet Assaymentioning
confidence: 99%
“…In Channa punctatus, sublethal concentrations of malathion (Kumar et al, 2010) and monocrotophos (Ali and Kumar, 2008) induced dose dependant DNA damage in gill, kidney and lymphocytes were reported during a study period of 1e29 d and 1e21 d respectively. Jamil et al (2005) reported genotoxic effect of monocrotophos in human lymphocytes in vitro employing Comet assay. A concentration dependant increase in the DNA damage was detected in the erythrocytes of Tilapia mossambica (Banu et al, 2001) and the gill cells of the bivalve, Meretrix ovum (Revankar and Shyama, 2009) after the exposure to monocrotophos.…”
mentioning
confidence: 99%